Studi Komparasi Strategi Everyone Is A Teacher Here Dan Snowball Throwing Terhadap Hasil Belajar Matematika Siswa Kelas V SD Muhammadiyah 1 Ketelan Surakarta Tahun 2015/2016 - Sari, Anggita Dewi Purnama (2016)
ABSTRACT Anggita Dewi Purnama Sari / A510120009. COMPARISON STUDY OF STRATEGY EVERYONE HERE IS A TEACHER AND SNOWBALL THROWING LEARNING OUTCOMES OF MATH CLASS V SD Muhammadiyah 1 Surakarta KETELAN YEAR 2015/2016. Essay. The Faculty of Education, University of Muhammadiyah Surakarta. January, 2016. This study aims to determine: (1) the effect difference between strategy Everyone Here Is A Teacher and strategies Snowball Throwing on learning outcomes math class V students of SD Muhammadiyah 1 Surakarta Ketelan year 2015/2016. (2) a better strategy between strategy Everyone Here Is A Teacher and strategies Snowball Throwing on learning outcomes math class V students of SD Muhammadiyah 1 Surakarta Ketelan know 2015/2016. This study included a quantitative study with an experiment model. The research subject graders VC and VD SD Muhammadiyah 1 Surakarta Ketelan. Data collection techniques using the technique of test, documentation, and interviews. Test instrument is used to test the validity and reliability testing. Data analysis technique using the t-test technique which preced analysis test prerequisite , that is the normality test using Liliefors and homogentitas test using Bartlett method. From the results of data analysis with a significance level of 5% there is no effect difference between strategy Everyone Here Is A Teacher and strategies Snowball throwing the learning outcomes math class V students of SD Muhammadiyah 1 Surakarta Ketelan with t_tabel> t_hitung, ie 2.00172> 1.2002. The mean scores between grade class are taught using the strategy Everyone Here Is A Teacher and classes are taught using the strategy of Snowball Throwing ie 76.9> 72.1. The conclusion of this study were (1) there is no effect difference between strategy Everyone Here Is A Teacher and strategies Snowball Throwing on learning outcomes math class V students of SD Muhammadiyah 1 Surakarta Ketelan year 2015/2016. (2) strategies Everyone Here Is A Teacher better than Snowball Throwing strategy against the results of students' mathematics learning class V SD Muhammadiyah 1 Surakarta Ketelan year 2015/2016.